PERENCANAAN TUBUH BENDUNGAN AIR PADANG GUCI KABUPATEN KAUR PROVINSI BENGKULU - Bagus Prasetya; Besperi Besperi; Muhammad Fauzi (Inersia: Jurnal Teknik Sipil, 2019)
Padang Guci Hulu Subdistrict has potential to meet the needs of sizeable water supply. It is supported by geographical location of Padang Guci Hulu Subdistrict which is in the tropical region where there are hight enough rainfall. However in general the problem arising in Padang Guci Hulu Subdistrict during dry season is the availability of raw water and irrigation water that very limited. The purpose of this research is to design a strong and safe dam body construction againts its stability control. Planning dam body uses design flood from synthetic hydrograph gamma I with a return period 1000 years of 224,66 meter3/second. This dam isplanned as high as 31,3 meter, with dam base elevation of + 405 meter, peak elevation + 436,30 meter, high surveillance 2,8 meter, the width of the dam crest 8,5 meter, upstream sloop 1 : 3, downstream sloop 1 : 2,25. The body design of the Air Padang Guci Dam has qualified for its stability control.